2020
DOI: 10.1111/ced.14451
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of acquired cutis laxa with urticarial eruption by diphenyl sulfone

Abstract: Click https://www.wileyhealthlearning.com/Activity/7155927/disclaimerspopup.aspx for the corresponding questions to this CME article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However, in the study of the dapsone effect in antihistamine refractory chronic idiopathic urticaria, VRDs occurred in only three patients in the placebo group (Morgan et al 2014 ). A higher dose of dapsone was required when the patient developed a tracheal infection, but the patient had no similar VRDs (Zheng et al 2021 ). We correlated dapsone to compete with the NLRP3 inflammasome (Lee et al 2020a ).…”
Section: Methodsmentioning
confidence: 99%
“…However, in the study of the dapsone effect in antihistamine refractory chronic idiopathic urticaria, VRDs occurred in only three patients in the placebo group (Morgan et al 2014 ). A higher dose of dapsone was required when the patient developed a tracheal infection, but the patient had no similar VRDs (Zheng et al 2021 ). We correlated dapsone to compete with the NLRP3 inflammasome (Lee et al 2020a ).…”
Section: Methodsmentioning
confidence: 99%
“…3 Chronic urticaria, dermatitis herpetiformis, Sweet syndrome, sarcoidosis, mastocytosis, and connective tissue disease are among the causative factors of ACL. 3 Recently, Zheng et al 5 and Takenaka et al 6 reported two very similar cases of generalized ACL developing in the setting of urticarial eruption, which were successfully treated with diphenyl sulfone. In the case of urticaria, infiltration of the neutrophils into the elastic fibers, increased elastase activity and dysfunction of elastase inhibitors, may cause fragmentation, thinning, and disorganization in ACL.…”
Section: Chronic Urticaria May Not Be As Innocent As We Think: a Rare...mentioning
confidence: 99%
“…In the case of urticaria, infiltration of the neutrophils into the elastic fibers, increased elastase activity and dysfunction of elastase inhibitors, may cause fragmentation, thinning, and disorganization in ACL. [5][6][7] Since dapsone inhibits calcium-dependent activities of neutrophils, therapeutic management may be achieved by the use of dapsone. 8 By looking at the examples of successful treatment with dapsone in ACL patients, we chose to start with dapsone.…”
Section: Chronic Urticaria May Not Be As Innocent As We Think: a Rare...mentioning
confidence: 99%